Die Mitte - Mucha, Stanislaw (Germany : Strandfilm Prduktions, 2004)
No less than a dozen towns within a radius of two-thousand kilometers claim the distinction of being the "center." In Austria's Braunau am Inn, where Japanese tourists are busy taking snapshots of Hitler 's birthplace, the director stops by a restaurant called "Mittelpunkt Europas" ("Center of Europe") and learns that Napoleon found his "center " in that very town. In Slovakia's Krahule, an angel helped to pinpoint the town's location. In the Polish town of Piatek, someone swears that the center has somehow disappeared, while in Lithuania's "Europos Centro" near Vilnius, one family sees Europe as a "monster" and the downfall of the Soviet Union as their worst misfortune. In the Western Ukrainian town of Rachiv we run into the last remaining Hasid who is buying the newspaper "Center of Europe." In its search for the geographical center of Europe this film follows a trail of errors, presumptions and bizarre self-assertions. It casts a particular light on eccentrics and visionaries, local patriots and continental utopians.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films